Stabiliojo centro veiksmažodžių šaknies struktūra - Kruopienė, Irena (Kalbotyra, 2000)
The article presents a structural description of the roots with the nucleus (vowel or diphtong), which has never changed in the basic forms of the verb, e. g. dìrba - dìrbo, dìrbti ‘to work’; rė̀kia - rė̀kė, rė̀kti ‘to shout’; plaũkia - plaũkė, plaũkti ‘to swim’. An analysis is given to the roots as well as to the initial and final consonant clusters. The comparison of the structure of verbal roots with Lithuanian and Latvian, has shown some differences, e. g. there are 14 structural models of the verbal roots, but there are 15 structural models of the Lithuanian and Latvian nominal roots.